2017
DOI: 10.1158/1078-0432.ccr-16-2554
|View full text |Cite
|
Sign up to set email alerts
|

Potential Predictive Value of TP53 and KRAS Mutation Status for Response to PD-1 Blockade Immunotherapy in Lung Adenocarcinoma

Abstract: Although clinical studies have shown promise for targeting programmed cell death protein-1 (PD-1) and ligand (PD-L1) signaling in non-small cell lung cancer (NSCLC), the factors that predict which subtype patients will be responsive to checkpoint blockade are not fully understood. We performed an integrated analysis on the multiple-dimensional data types including genomic, transcriptomic, proteomic, and clinical data from cohorts of lung adenocarcinoma public (discovery set) and internal (validation set) datab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

46
697
6
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 799 publications
(752 citation statements)
references
References 52 publications
46
697
6
3
Order By: Relevance
“…As with hypermutated, microsatellite-high tumors of the colon, endometrium, and other sites, highly mutated lung cancers with smoking-related, transversion-high signatures appear significantly more likely to overexpress PDL1 and to respond to PD-1 inhibition. 36,91 Mechanistically, smoking-related transversion mutations in non-small-cell lung carcinoma contribute to neoantigen formation with resulting T-cell recruitment. IFN- γ release from tumor-infiltrating T cells may trigger adaptive upregulation of tumor PD-L1 and engagement with PD-1 expressing T cells, preventing immune attack.…”
Section: Non-small-cell Lung Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…As with hypermutated, microsatellite-high tumors of the colon, endometrium, and other sites, highly mutated lung cancers with smoking-related, transversion-high signatures appear significantly more likely to overexpress PDL1 and to respond to PD-1 inhibition. 36,91 Mechanistically, smoking-related transversion mutations in non-small-cell lung carcinoma contribute to neoantigen formation with resulting T-cell recruitment. IFN- γ release from tumor-infiltrating T cells may trigger adaptive upregulation of tumor PD-L1 and engagement with PD-1 expressing T cells, preventing immune attack.…”
Section: Non-small-cell Lung Carcinomamentioning
confidence: 99%
“…Some studies have failed to identify a correlation between tumor genotype and immunoprofile, 92 while others have suggested that KRAS/TP53 mutation status predicts for tumor adaptive immune resistance that may be amenable to PD-1 pathway blockade. 91 STK11 loss-of-function mutations, which occur in 10–15% of lung adenocarcinomas, tend to co-occur with KRAS mutations, appear to promote recruitment of neutrophils to the tumor and exclude T-cell infiltrates, 9395 and thus may confer relative resistance to immune checkpoint blockade. Therefore, it is likely that tumor genetics have an important role in defining the non-small-cell lung carcinoma tumor immune response.…”
Section: Non-small-cell Lung Carcinomamentioning
confidence: 99%
“…Son yıllarda yapılan pek çok PD-L1 immünhistokimya uzlaşma çalışması da bu karışıklığı çözmeye yönelik adım atmayı hedeflemektedir (54). Tümör hücrelerinde izlenen PD-L1 immünhistokimyasal pozitifliğinin, sigara kullanımı, artmış somatik mutasyonlar ve yeni antijen ekspresyonlarıyla karakterize TP53 ve KRAS gibi mutasyonlarla birlikteliği, yüksek mutasyon oranına sahip tümörlerde immünoterapinin daha etkili olacağı düşüncesini desteklemektedir (55,56).…”
Section: İmmünoterapi (Pd1/pd-l1)unclassified
“…Thus, the purpose of recent studies has been the identification of immune-editing of T cells during tumor development, as well as the determination of their potential applications for tumor-specific immunotherapy 164 . …”
Section: Targeting the Immune Systemmentioning
confidence: 99%
“…In one study, the efficacy of immune checkpoint inhibitors among NSCLCL patients was found to correlate with the KRAS mutation as a molecular smoking signature 165 . Other evidence indicates that the co-mutation of TP53 and KRAS in lung adenocarcinoma can be exploited as a potential predictive marker for effective immune checkpoint blockade immunotherapy 164 . Clinical trials have also been initiated for the KRAS -G12D-specific cancer vaccine TG01/ GM-CSF either alone or combined with gemcitabine.…”
Section: Targeting the Immune Systemmentioning
confidence: 99%